Standing Height and its Estimation Utilizing Sitting Height Measurements in Adolescents from the Western Region in Kosovo - Bojan Masanovic; Fitim Arifi; Jovan Gardasevic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
The purpose of this research is to examine standing height in both Kosovan genders in the western region of as well as its association with sitting height, as an alternative to estimating standing height. A total of 664 individuals (338 male and 326 female) participated in this research. The anthropometric measurements were taken according to the ISAK protocol. The relationships between standing height and sitting height were determined using simple correlation coefficients. A comparison of means of standing height and sitting height between genders was performed using a t-test, while linear regression analyses were carried out to examine the extent to which sitting height can reliably predict standing height. The results reveal that Western Kosovan males are 179.71±6.00 cm tall and have a sitting height of 94.79±3.60 cm, while Western Kosovan females are 166.26±5.23 cm tall and have a sitting height of 90.28±3.25 cm. The results have shown that both genders made Western-Kosovans tall and somewhat taller than the general Kosovan population. Moreover, the sitting height reliably predicts standing height in both genders but not arm span sufficiently reliably. This study also confirms the necessity of developing separate height models for each region in Kosovo as the results from Western-Kosovans do not correspond to the national values.